A novel device to improve robustness of end plate beam-column connections. (December 2020) - Shaheen, Mohamed A.; J. Foster, Andrew S.; Cunningham, Lee S.
Abstract: Achieving a robust connection is a challenging task for design engineers since the connection's strength is inseparably linked to its ductility. This paper presents a novel approach that separates designing bolted connections for strength from designing for ductility. By inserting a steel sleeve with a designated length, thickness and wall curvature between the end plate and the washer, the load path between the end plate and the bolts can be interrupted, promoting a more ductile response. End plate connections with various sleeve geometries are numerically investigated using a validated FE model to prove the concept of the proposed method. The proposed system substantially enhances the rotational capacity up to 2.92 times that of the standard connection. An elastic response consistent with standard connections is maintained indicating that the proposed system is compatible with existing codified elastic design approaches without modification.